2009
DOI: 10.1016/j.cardfail.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury in Autonomic, Emotional, and Cognitive Regulatory Areas in Patients With Heart Failure

Abstract: Background-Heart failure (HF) is accompanied by autonomic, emotional, and cognitive deficits, indicating brain alterations. Reduced gray matter volume and isolated white matter infarcts occur in HF, but the extent of damage is unclear. Using magnetic resonance T2 relaxometry, we evaluated the extent of injury across the entire brain in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 64 publications
13
160
1
Order By: Relevance
“…Heart failure patients showed a marked and sustained increase in heart rate to the cold pressor stimulus compared to the decrease seen in controls, and a very transient decrease in diastolic pressure. A concomitant increase in right insular fMRI signal was noted compared with controls, and these overlapped with the areas of structural change seen on MRI in previous studies (352,353). Similar overlap was noted for the right ventral frontal cortex, thalamus, right cingulate, and hypothalamus, areas, which also showed an increase in signal in heart failure patients; the cerebellar signal increase seen in heart failure, however, did not overlap areas showing structural changes.…”
Section: Human Functional Studiessupporting
confidence: 78%
See 1 more Smart Citation
“…Heart failure patients showed a marked and sustained increase in heart rate to the cold pressor stimulus compared to the decrease seen in controls, and a very transient decrease in diastolic pressure. A concomitant increase in right insular fMRI signal was noted compared with controls, and these overlapped with the areas of structural change seen on MRI in previous studies (352,353). Similar overlap was noted for the right ventral frontal cortex, thalamus, right cingulate, and hypothalamus, areas, which also showed an increase in signal in heart failure patients; the cerebellar signal increase seen in heart failure, however, did not overlap areas showing structural changes.…”
Section: Human Functional Studiessupporting
confidence: 78%
“…Why there should be such a right lateralized effect is also unclear. In a subsequent voxel-based T2 relaxometry study of heart failure patients (this technique measures free-water content with T2 values increasing in the presence of structural changes), abnormalities were detected in the right AI, left posterior insula, the anterior cingulate, caudal ventral premotor cortex, and posterior cingulate interpreted as being related to structural damage in these regions (352). The underlying pathology is however, unclear as relaxation changes such as these can be seen in a variety of processes including gliosis, cell loss, cell injury, edema, and demyelination (119).…”
Section: Human Functional Studiesmentioning
confidence: 99%
“…These cognitive deficits, found on neuropsychological testing, have been validated by studies using neuroimaging techniques in which HF patients have been found to have diminished gray matter volume in the insular cortex, frontal cortex, parahippocampal gyrus, cingulate, cerebellar cortex, and deep cerebellar nuclei compared with age-matched healthy individuals. 173,174 Additionally, HF patients have been shown to have significantly reduced regional blood flow in the precuneus and cunea, the right lateral temporoparietal cortex, and the posterior cingulated gyrus compared with age-matched healthy individuals. 175 Self-care is a decision-making process that uses the prefrontal cortex.…”
Section: Impaired Cognitionmentioning
confidence: 99%
“…Memory loss in HF is believed to result from inadequate cerebral perfusion and increased microemboli. 5,6 Compared with age-matched healthy persons, HF patients have neuronal loss 7 with reduced axonal integrity 8 and altered myelin structure 8 in hippocampal and cerebellar brain regions. 7,8 In addition to specific HF-related pathophysiology, age contributed to cognitive dysfunction and mortality among HF patients.…”
Section: Introductionmentioning
confidence: 99%